Pengaruh Pendapatan, Beban dan Ukuran Perusahaan Terhadap Beban Pajak dengan EBIT sebagai Pemoderasi - Hu, Catherine; Merlin, Christine; Yapin, Ehtan (Media Akuntansi Perpajakan, 2025)
This study aims to analyze the effect of revenue, operational expenses, and firm size on tax burden with EBIT (Earnings Before Interest and Taxes) as a moderating variable. The study uses secondary data from the financial statements of companies listed on the Indonesia Stock Exchange (IDX) for the period 2020 to 2023. The sample was selected using a purposive sampling method, focusing on non-financial companies with complete financial data. The analysis method employed is Partial Least Squares - Structural Equation Modeling (PLS-SEM), assisted by SmartPLS software. The results show that revenue, operational expenses, and firm size do not have a significant effect on the tax burden. However, EBIT has a significant moderating effect, indicating that operating income plays a crucial role in influencing tax burden management. These findings emphasize the importance of operational profitability in tax planning strategies, especially in the post-pandemic economic context.